The role of internal audit in Information Technology Management - Akynov, D.M.; Rassulova, А.М.; Yeveskina, Zh.T.; Khishauyeva, Zh.T.; Akhmetova, A.B. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this study is to study the role of internal audit in information technology management. It also explores contemporary factors influencing information technology internal audit, the rationale for establishing and maintaining internal audit capabilities, and describes some of the potential benefits organizations expect from wellmanaged internal audit programs by describing the structural and operational features of internal audit programs that include IT audits in their field. This article discusses the typical location of the internal audit service in the organizational structure and its relationship with the governing bodies. It also describes some of the characteristics of internal auditors and the related skills and experience that auditors need to perform their job effectively. Methods: The study used such scientific methods as induction, deduction, generalization, grouping, classification, comparative analysis and justification, statistical analysis, as well as correlation and variance analysis. Findings: Maintaining an effective internal audit program also helps organizations demonstrate their commitment to the principle of due diligence by demonstrating that they act competently and laboriously in relation to the functioning and maintenance of their internal control systems. Providing evidence of due diligence provides important information for investors and business partners, and can also provide legal protection in disputes related to liability or business practices. Conclusions: According to the results of the study obtained, the increase in labor productivity directly depends on the digitalization of the population. Therefore, we get a certain result in enterprises and government agencies by identifying persons responsible for the development of information management of the population, that is, information technology in their structures, and by conducting an appropriate internal audit.